Renewal of Islamic Religious Education in Banten: Majelis Taklim - Samudi Samudi; Ali Nurdin (AL-ISHLAH: Jurnal Pendidikan, 2022)
The study's overarching objective is to investigate, analyze, and formulate the renewal of Majelis Taklim's curriculum, teaching and learning, educators, and educational staff. This study used a phenomenological research method and a qualitative strategy. Research participants include the leader, secretary, and treasurer of Majelis Taklim. Observation, in-depth interviews, and documentation are all techniques for gathering data. The study's findings are as follows: the coaching factor of local government policies affects the renewal of Islamic educational institutions, but cultural resistance from each of these Islamic religious education institutions slows the process down. This is true even though the renewal process is ongoing and has already happened in the curriculum, learning, teachers, and education staff of the Majelis Taklim organization. Among the developments it incorporates are new learning materials, new learning rules, new media and methods, new acceptance criteria and legality of teaching and educational staff, and a new management structure with the appropriate number of members.